Exploring the Lived Experiences of Filipino Smallholder Farmers under Contract Rice Farming within a Neoliberal Context - John Patrick Habacon (Recoletos Multidisciplinary Research Journal, 2025)
Background: Contract farming is expanding in the Philippines, primarily driven by adopting neoliberal policies. While this model benefits farmers, it also raises significant concerns. This study examines the implications of contract farming in the rice farming sector, focusing on smallholder rice farmers' experiences, challenges, and coping strategies. Methods: Through in-depth interviews and an ethnographic approach including observations of five farmers, the study reveals their dependence on contract farming due to lack of initial capital and the attractive market price of hybrid rice. Results: Three key structural themes emerged: (1) High Hopes – the motivations and perceived benefits of contract farming; (2) Covert Exploitation – the hidden struggles including high input costs, delayed payments, and lack of support during disasters; and (3) Resistance and Adjustments – the farmers' adaptive strategies to cope with these challenges. Conclusion: Farmers often enter contract arrangements due to limited capital and the promise of higher returns from hybrid rice that is grown mainly for export. This creates a troubling paradox: the country exports rice while facing food insecurity. The study calls for fair and sustainable policies to empower and support smallholder rice farmers, promoting their autonomy and reducing vulnerability.